2011
DOI: 10.3389/fmicb.2011.00102
|View full text |Cite
|
Sign up to set email alerts
|

The Pathobiology of Neisseria gonorrhoeae Lower Female Genital Tract Infection

Abstract: Infection and disease associated with Neisseria gonorrhoeae, the gonococcus, continue to be a global health problem. Asymptomatic and subclinical gonococcal infections occur at a high frequency in females; thus, the true incidence of N. gonorrhoeae infections are presumed to be severely underestimated. Inherent to this asymptomatic/subclinical diseased state is the continued prevalence of this organism within the general population, as well as the medical, economic, and social burden equated with the observed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
44
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 142 publications
(171 reference statements)
0
44
0
Order By: Relevance
“…However, the decreased expression of norB observed in the Ng-ntrX mutant also likely played a predominant role in the impaired ability of mutant gonococci to survive within pex cells, as previous data indicate that nitric oxide utilization plays a paramount role in promoting gonococcal survival within pex cells (64,65). The human and bacterial responses driving the cervical tissue-gonococcus dynamic are complex (65). Therefore, additional, alternative adaptive responses controlled by the NtrYX TCS may have a contributory role in promoting the intracellular survival and growth of gonococci in the pex cell model of infection.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…However, the decreased expression of norB observed in the Ng-ntrX mutant also likely played a predominant role in the impaired ability of mutant gonococci to survive within pex cells, as previous data indicate that nitric oxide utilization plays a paramount role in promoting gonococcal survival within pex cells (64,65). The human and bacterial responses driving the cervical tissue-gonococcus dynamic are complex (65). Therefore, additional, alternative adaptive responses controlled by the NtrYX TCS may have a contributory role in promoting the intracellular survival and growth of gonococci in the pex cell model of infection.…”
Section: Discussionmentioning
confidence: 81%
“…Hence, one of the factors that may have contributed to the failure of the gonococcal ntrX mutant to survive within pex cells may be a lowered level of cytochrome cbb 3 activity. However, the decreased expression of norB observed in the Ng-ntrX mutant also likely played a predominant role in the impaired ability of mutant gonococci to survive within pex cells, as previous data indicate that nitric oxide utilization plays a paramount role in promoting gonococcal survival within pex cells (64,65). The human and bacterial responses driving the cervical tissue-gonococcus dynamic are complex (65).…”
Section: Discussionmentioning
confidence: 81%
“…29 Similarly, infection of epithelial cells in the vagina and cervix has been demonstrated to be a mechanism by which Gonorrhea infection occurs. 30 Human beta defensins are a component of the innate immune system and produced by epithelial cells. The observed increase in Defensin 1 with VP may serve to enhance the antimicrobial properties of the epithelial barrier, preventing a breakdown in the epithelial barrier from infectious processes.…”
Section: Discussionmentioning
confidence: 99%
“…Both men and women are affected. STDs constitute a hidden epidemic of enormous physical, psychological, and economic consequences (4, 5, 12). Our data revealed that gonococcal infections could occur for asymptomatic women who had not any risk factor, and its incidence is low.…”
Section: Discussionmentioning
confidence: 99%
“…Health complications resulting from gonorrhea disease occur mainly in women, and are largely assigned to the predominately asymptomatic nature of the lower genital tract infection. Untreated, subclinical infection of the cervix can lead to upper genital tract involvement and, potentially, to infertility (4, 5). Similar to Chlamydia trachomatis, 80% of women (though only 10% of men) infected with Neisseria gonorrhea are asymptomatic, and the most common and serious complications of the infection are also infertility, ectopic pregnancy, and pelvic inflammatory disease (5, 6).…”
Section: Introductionmentioning
confidence: 99%